Analisis Collaborative Governance dalam Pembangunan Kawasan Desa Wisata (Studi pada Desa Wisata Ekang di Kabupaten Bintan) - Dory Gurvantry; Andres Febriansah; Junus Tampubolon (Policy, Law and Political Research Center, 2022)
Tourism is one of the Government's mainstay sectors in an effort to improve the economy. One sector that attracts visitors is the Ekang Tourism Village in Bintan Regency. Seeing that the position of the village is very strategic and beautiful in its natural beauty, so this tourist village must be able to use its strength to take advantage of opportunities in developing tourist villages. This is evidenced by the state of the power of the uniqueness and enchanting natural beauty. Besides that, the beautiful environment is also one of the strengths in the region. To further support its development, competent human resources (HR) are needed, intensive partnership or cooperation patterns, promotive government activities in villages. This study aims to see how the roles of stakeholders are involved and the development strategy of Ekang Bintan Regency. The result of the research is that stakeholders have an interrelated role in the development and how the government pattern in developing regions will have an impact on the progress of the region concerned. In this case, Bintan Regency implements Collabrative Governance in developing its tourism sector.